A Monte Carlo–Quantum Mechanics Study of a Solvatochromic ?* Probe - Caroli-Rezende, M; Dominguez-Caru, M (Springer Verlag, 2016)
The solvation and the solvatochromic behavior of 5-(dimethylamino)-5′-nitro-2,2′-bithiophene 1, the basis of a π* scale of solvent polarities, was investigated theoretically in toluene, dichloromethane, methanol and formamide with a Monte Carlo and quantum mechanics (QM/MM) iterative approach. The calculated transition energies of the solvatochromic band of 1, obtained as averages of statistically uncorrelated configurations, including the solute and explicit solvent molecules of the first solvation layer, besides showing good agreement with the experimental transitions, reproduced very well the positive solvatochromism of this probe in various solvents. © 2016, Springer-Verlag Berlin Heidelberg.